Ionic currents in cultured rat hypothalamic neurones. - Müller, Thomas; Misgeld, Ulrich; Swandulla, Dieter (The journal of physiology, 1992)
1. Dissociated neurones from embryonic rat hypothalamus were grown for several weeks in culture where they formed complex networks. These synaptically coupled networks were capable of generating synchronized bursting activity. Voltage-activated membrane currents were studied in these neurones using a patch clamp in the whole-cell configuration. 2. Outward currents were carried by K+ ions and consisted of an inactivating and a non-inactivating component. These components were similar to the transient K+ current (IA) and the delayed rectifier current (IK) reported in neurones from the postnatal rat hypothalamus. Application of Zn2+ (1 mM) blocked the transient component completely while reducing the non-inactivating component by only approximately 20%. 3. Inward currents were carried by Na+ and Ca2+ ions. Rapidly activating transient Na+ currents were activated at approximately -25 mV. TTX entirely blocked these currents at low concentration (300 nM). Voltage sensitivity of the Na+ conductance was 5.8 mV per e-fold change with half-maximal activation occurring at -8 mV. Na+ current kinetics could be well described by the Hodgkin-Huxley model (m3h). 4. With depolarizing pulses from a holding potential of -80 mV two Ca2+ current components with different ranges of activation were identified. Low voltage-activated (LVA, T-type) Ca2+ currents were activated at approximately -50 mV. High voltage-activated (HVA; also called L- or N-type) Ca2+ currents were observed at membrane potentials more positive to approximately -30 mV. LVA Ca2+ currents were observed in hypothalamic neurones that had developed a network of dendritic processes in the course of several weeks in culture. Activation and inactivation time constants of LVA Ca2+ currents were 15-25 ms and 30-100 ms (-30 to -45 mV). In contrast to HVA Ca2+ currents, no LVA Ca2+ currents were seen in neuronal somata obtained from the network cultures by mechanical dissociation. This suggests that most of the LVA Ca2+ channels are located on the dendritic tree rather than on the soma membrane. 5. HVA Ca2+ currents were maximal between 0 and +10 mV (external [Ca2+] = 5 mM). The time-to-peak was in the range of 1.7-5.4 ms (+30 to -10 mV). Tail currents following repolarization decayed monoexponentially with a time constant of approximately 210 microseconds. During 500 ms depolarizations, 90% of the current inactivated. The time course of inactivation showed two time constants of approximately 40 and approximately 700 ms.(ABSTRACT TRUNCATED AT 400 WORDS)
Gesehen am 26.04.2021